Interactions of marine protected species with artisanal fisheries in the Parque Natural do Sudoeste Alentejano e Costa Vicentina (PNSACV) and adjacent classified areas (SPAs and SACs) - Alexandre, Teresa Sofia Ferreira (2019)
Tese de mestrado, Ecologia Marinha, Universidade de Lisboa, Faculdade de Ciências, 2019